Strategic Competence in Authentic Intercultural Interaction: The Role of Interaction Format in an Indonesian EFL Context - Salisa Afifah Qurrota Ayun; Muhammad Handi Gunawan (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
This study investigates how Indonesian EFL students deploy communication strategies in authentic intercultural interaction and how such engagement shapes their communicative confidence. Data were collected through classroom observations during six sessions, using two interaction formats (discussion and presentation), and through semi-structured interviews with six participants. The analysis identified patterns in strategy use, strategic awareness, interaction dynamics, and affective outcomes. Findings indicate that strategic competence manifested strongly through multimodal resources, particularly gesture, which appeared more frequently in discussion settings. Discussion format also promoted greater strategic diversity and collaborative mediation. Despite effective strategy use, students demonstrated limited strategic awareness but reported increased communicative confidence following authentic interaction. These findings demonstrate that discussion-oriented, meaning-focused authentic interaction fosters multimodal strategic competence and communicative confidence in EFL learners, supporting the design of intercultural programs that prioritize student agency, peer collaboration, and exposure to diverse English varieties over form-focused instruction.